Donor Genotype in the Interleukin-7 Receptor α-Chain Predicts Risk of Graft-versus-Host Disease and Cytomegalovirus Infection after Allogeneic Hematopoietic Stem Cell Transplantation - Kielsen, Katrine (Front Immunol, 2018)
The efficacy of allogeneic hematopoietic stem cell transplantation (HSCT) is challenged by acute and chronic graft-versus-host disease (aGVHD and cGVHD) and viral infections due to long-lasting immunodeficiency. Interleukin-7 (IL-7) is a cytokine essential for de novo T cell generation in thymus and peripheral T cell homeostasis. In this study, we investigated the impact of the single nucleotide polymorphism rs6897932 in the IL-7 receptor α-chain (IL-7Rα) which has previously been associated with several autoimmune diseases. We included 460 patients undergoing allogeneic HSCT after a myeloablative conditioning. Patients had a median age of 26.3 years (0.3–67.0 years), and 372 (80.9%) underwent HSCT for malignant diseases. Donors were matched sibling donors (n = 147), matched unrelated donors (n = 244) or mismatched unrelated donors (n = 69), and the stem cell source were either bone marrow (n = 329) or peripheral blood (n = 131). DNA from donors was genotyped for the IL-7Rα single nucleotide polymorphism (SNP) rs6897932 using an allele-specific primer extension assay (CC: n = 252, CT: n = 178, TT: n = 30). The donor T allele was associated with a higher risk of grades III–IV aGVHD (HR = 2.0, 95% CI = 1.1–3.8, P = 0.034) and with significantly increased risk of extensive cGVHD (HR = 2.0, 95% CI = 1.1–3.6, P = 0.025) after adjustment for potential risk factors. In addition, the TT genotype was associated with a higher risk of cytomegalovirus (CMV) infection post-transplant (HR = 2.4, 95% CI = 1.2–4.3, P = 0.0068). Numbers of T cells were significantly higher on day +60 in patients receiving a rs6897932 TT graft (CD3+: 109% increase, P = 0.0096; CD4+: 64% increase, P = 0.038; CD8+: 133% increase, P = 0.011). Donor heterozygosity for the T allele was associated with inferior overall survival (HR = 1.7, 95% CI = 1.2–2.3, P = 0.0027) and increased treatment-related mortality (HR = 2.3, 95% CI = 1.3–4.0, P = 0.0047), but was not associated with the risk of relapse (P = 0.35). In conclusion, the IL-7Rα rs6897932 genotype of the donor is predictive of aGVHD and cGVHD, CMV infection, and mortality following HSCT. These findings indicate that IL-7Rα SNP typing of donors may optimize donor selection and facilitate individualization of treatment in order to limit treatment-related complications.